The opioid crisis is driving mortality among under-served people living with HIV in British Columbia, Canada - Kate A. Salters; Stephanie Parent; Valerie Nicholson; Lu Wang; Paul Sereda; Tatiana E. Pakhomova; Mia Kibel; William Chau; Kalysha Closson; Surita Parashar; Rolando Barrios; Julio S. G. Montaner; et al. (BMC, 2021)
Abstract Introduction Universal provision of effective antiretroviral medication has been essential to reduce mortality, increase longevity, and reduce onward transmission of HIV. This study aims to illuminate persistent threats to the health and longevity of under-served PLWH in British Columbia (BC), Canada. Methods Between 2007 and 2010, 1000 PLWH across BC were enrolled in the Longitudinal Investigation into Supportive and Ancillary health services (LISA) study and completed a cross-sectional survey on their HIV-care experiences and healthcare engagement. The sample generally reflects an under-served population of PLWH. A linkage to the provincial Vital Statistics registry is used in this analysis in order to examine overall mortality and cause-specific mortality trends; probability of death was modeled using logistic regression for participants with ongoing clinical monitoring (n = 910). Results By June 2017, 208 (20.8%) participants had died. The majority of deaths 57 (27.4%) were attributed to drug-related complications or overdoses, 39 (18.8%) were attributed to HIV-related complications, and 36 (17.3%) to non-AIDS-defining malignancies. We observed elevated odds of death among PLWH who smoked tobacco (aOR: 2.11, 95% CI: 1.38, 3.23), were older (aOR: 1.06 per one-year increase, 95% CI: 1.04, 1.08), indicated heavy alcohol consumption (aOR: 1.57, 95% CI: 1.11, 2.22), and reported unstable housing (aOR: 1.96, 95% CI: 1.37, 2.80); while higher CD4 cell count was protective (aOR: 0.87 per 100-unit increase, 95% CI: 0.79, 0.94) as was male gender), though non-significant (aOR: 0.73, 95% CI: 0.49, 1.07). Conclusions Overdose is - the leading cause of mortality among a cohort of under-served PLWH in BC, Canada. Public health efforts to end the HIV epidemic and support the health and well-being of PLWH are being thwarted by persistent health inequities and the enormous and persistent risks facing people who use drugs. Integrated low-barrier primary care is essential for supporting under-served PLWH, and safe drug supply is needed to support PLWH who use drugs.